Effect of Intraoperative Epidural Steroids to Prevent Post-op Pain and Length of Hospital Stay in Patients undergoing Lumbar Discectomy Presenting in Department of Neurosurgery at Bolan Medical College - Abdul Hameed, Aman Ullah Khan Kakar, Khushal Khan, Attiq Ur Rehman, Irfan Adil (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Approximately 80% of individuals experience at least one episode of low back pain in their lifetime. Due to its widespread occurrence and considerable impact on disability, low back pain results in annual expenses surpassing 100 billion in the United States.1,2 Among the extensive differential diagnoses for low back pain, the primary cause is often attributed to intervertebral degeneration, which results in degenerative disc disease and lumbar disc herniation.2 Objective: To compare effect of intraoperative use of epidural steroids with normal saline in lumbar discectomy in terms of post-operative pain and length of hospital stay Setting: Neurosurgery Department, Bolan Medical College/ teaching Hospital, Quetta Duration of Study: From 17th April 2022 to 16th April 2023. Study Design: Randomized Controlled Trial Material and Methods: In this study, a total of 120 patients were examined, with 60 individuals assigned to each group. The patients were randomly allocated into two groups through blocked randomization, each comprising 60 participants. Group A received intraoperative epidural methylprednisolone acetate, while Group B was administered only normal saline. The effectiveness of the treatment was assessed from the day of surgery until the patient’s discharge, utilizing the Visual Analog Scale (VAS) for pain measurement and evaluating the total duration of hospital stay Results: Our study shows that mean age in Group A mean age was 44 years with SD ± 12.77. Whereas mean age in Group B mean age was 46 years with SD ± 13.12. In Group A 34 (57%) patients were male and 26 (43%) patients were female. Where as in Group B 36 (60%) patients were male and 24 (40%) patients were female. More over Group A (epidural steroids) was effective in 56 (93%) patients while Group B (normal saline) was effective in 40 (67%) patients. Conclusion: Our study concludes that epidural steroids are more effective than normal saline after lumbar discectomy in term of post-operative pain and hospital stay. Keywords: Effectiveness, intraoperative use of epidural steroids, normal saline, discectotmy, lumber disc herniation